POTENTIAL USE OF CARIUM CARVI AND CURCUMA LONGA FOR THE REMEDY OF SKIN AND SOFT TISSUES PATHOGENS - H. Khan; J. Khan; S. Gul; M. I. Khan; H. Khan; M. A. Khan (Journal of Animal and Plant Sciences, 2020)
The Pathogens responsible for the skin and soft tissue infections are often prone to develop resistance to antibiotics. A good alternative to this resistance is the use of folk medicine. For this purpose two plants Carium carvi and Curcuma longa, used in folk medicine were tested against the selected pathogens, Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aerugenosa and Streptococcus pyogenes. The pathogenswere collected from the patients having skin and soft tissues infections. The isolated pathogens were identified through microscopic studies followed by biological tests using Sigma Aldrich KGaA Merck kit protocol. These plant materials were extracted with MeOH and then portioned among different solvents, based on their polarity. These extracts were then applied against the selected pathogens, using well diffusion assay method and the minimum inhibitory concentration (MIC). The results showed marked antibacterial activity in the chloroform and ethyl acetate extract (18 mm zone of inhibition each) of Carium carvi seeds while the chloroform extract of Curcuma longa showed (21 mm zone of inhibition) promising results. Sensitivity of various extracts of the plant in a concentration dependent manner with significant MIC values was determined. Our findings showed that the extracts of C. longa and C. carvi seeds possess strong antibacterial effects against clinically isolated skin and soft tissue pathogens.
Keywords: Carium carvi; Curcuma longa; Skin diseases; Pathogens; Antibacterial activity